The Economics of Terrorism and Counter-Terrorism: A Survey (Part I) - Friedrich Schneider; Tilman Brück; Daniel Meierrieks (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
This survey provides an in-depth analysis of existing research on the economic analysis of terrorism and counter-terrorist measures. First the existing evidence on the causes of terrorism is analyzed, then we consider the evidence of the consequences of terrorism and we demonstrate why it is important to regarding of the issue of counter-terrorism policy. Moreover the survey presents the existing knowledge on the interrelation between the economy and the issue of security and it incorporates analysis the level of knowledge about the causal chains between security and the economy. Also it focuses on perspective and methodologies from the discipline of economics but also refers to research from related disciplines (sociology, political science). It also assembles the knowledge on the impact of terrorism on the economy as reflected in macro-economic variables and its impact on specific sectors. Furthermore it assesses how potential an actual terrorist event determine consumer and producer behaviour, public policy, as well as terrorist responses to these policies. Finally a European perspective on the terrorism security annexes is discussed and here we analyze the causes of terrorism in Europe.
info:eu-repo/grantAgreement/EC/FP7/218105
Keywords: K42; H56; O17; 330; risk; insecurity; survey; terrorism; counter-terrorism; security economics